EFFECT OF SERVICE QUALITY, PRICE AND PROMOTION ON CUSTOMER LOYALTY IN PT. GREAT SEASONS BATAM - Wasiman; Mauli Siagian (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
Batam as a region with brand a very well-knownthat is due to the geographic location close to Singapore to make Batam into the area local and foreign tourist destinations. Along with these developments, there are many service companies in Batam City. PT. Great Seasons Batam is one of the companies in the field ofservices travel which is located at Ruko Fanido Blok O No 15 Tanjung Uncang Batam. The purpose of this study was to determine the effect of service quality, to determine the price and promotion carried out by PT. Great Seasons. The problems that occur in PT. Great Seasons is that the quality of service is still not good and there are still many complaints felt by customers, not only that, other problems are that prices are still high and promotions are minimal. The method used is by distributing questionnaires to customers of PT. Greats Seasons in Batam. The number of respondents was 133 respondents. The results of the study show that 1) service quality has a significant effect on customer loyalty. 2) Price has an effect on customer loyalty and promotion has no effect on customer loyalty. F test results showed that the variables of service quality (X1) Price (X2) and Promotion (X3) influence on Customer Loyalty PT. Great Seasons in Batam. R Square Test Results showed that the variables of servicequality, price and promotion can be explained by 85% while 15% is determined by other variables outside the research conducted